An international finance reader - Das, Dilip K. (London ; New York : Routledge, 2003)
Leading world economic experts examine topical issues of international finance such as globalization, multilateral financial institutions and capital flows to emerging economies. Ideal for students, businesspeople and policy makers.
Includes bibliographical references and index.
oif 17/09/15
Loan
Keywords: International finance